Optimization of electrospray ionization-mass spectrometric parameters for the analysis of chloramphenicol in fish using LC-MS/MS and experimental design. - Deniola, Emmanuel G. (University of the Philippines Visayas, 2018)
In this study, a 33 full factorial experimental design was used for the optimization of the electrospray ionization-mass spectrometric (ESI-MS) parameters of the LC-MS/MS interface for the analysis of chloramphenicol in fish. The parameters involved are the nebulizing gas flow rate, drying gas flow rate, and ESI probe position. These factors are crucial in improving the ionization efficiency of the equipment and the sensitivity of the method. Improving of the ionization process in the interface produces more analyte precursor ions which results to an increased number of product ions needed for the quantification in the LC-MS/MS system. Maximum analyte response (peak area per MRM transition and peak height) was achieved when the nebulizing gas flow rate, drying gas flow rate, and ESI probe position were set to 3 L/min, 11 L/min and 0 position, respectively. The DOE-optimized method was compared to the existing OFAT-optimized method, previously developed at the Bureau of Fisheries and Aquatic Resources-Regional Fisheries Laboratory VI. Analytical performance was evaluated in terms of ionization efficiency (peak area, peak height, and signal-to-noise ratio) as well as sensitivity (LOD, LOQ, and detection capability) using standard solutions and spiked fish samples. The DOE-optimized method generated higher analytical response (peak area, peak height, and signal-to-noise ratio). In terms of sensitivity, the DOE-optimized method outperformed the OFAT-optimized method due to its lower LODS and LOQs, higher signal-to-noise ratios, and increased detection sensitivity at low concentrations.